2018
DOI: 10.1145/3274373
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Real-Time Collaboration in Crowd-Powered Systems Through a UI Design Tool

Abstract: Real-time collaboration between a requester and crowd workers expands the scope of tasks that crowdsourcing can be used for by letting requesters and crowd workers interactively create various artifacts (e.g., a sketch prototype, writing, or program code). In such systems, it is increasingly common to allow requesters to verbally describe their requests, receive responses from workers, and provide immediate and continuous feedback to enhance the overall outcome of the two groups' real-time collaboration. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous work showed such disagreements in part-of-speech tagging [36], disagreements because of lack of labelers' expertise in the area [29,41], and disagreements on controversial matters [21] (e.g., use of "annexation" vs "liberation" when describing a conflict based on the political and ideological stand of the editor). Disagreements on the question of neutrality is a reflection of the pluralist voices of a society [9].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed such disagreements in part-of-speech tagging [36], disagreements because of lack of labelers' expertise in the area [29,41], and disagreements on controversial matters [21] (e.g., use of "annexation" vs "liberation" when describing a conflict based on the political and ideological stand of the editor). Disagreements on the question of neutrality is a reflection of the pluralist voices of a society [9].…”
Section: Resultsmentioning
confidence: 99%
“…Also, differences in expertise levels can impede crowd workers' collaborative effectiveness. Specifically, a crowd worker team's use of modifiable shared artifacts to scaffold ideas between team members and crowd workers was shown to improve collaboration (Lee et al, 2018). Research has found that peer production group members use other's history of project activity to form impressions of other's expertise (Marlow, Dabbish, & Herbsleb, 2013).…”
Section: Technology As Creation Mediummentioning
confidence: 99%
“…Project Planning [25] Requirement Management [20] Programming/Coding [14,21,37] Software Testing [7,17] Software Integration [7] Debugging [40] Software Evolution [40] Generic development [8][9][10][11][12][13]15,16,18,19,[22][23][24][26][27][28][29][30][31][32][33][34][35][36]38,39,41,42] The activities mentioned in Table 5 are the only software engineering activities where freelancers were involved as reported by the literature studies. The formulation of the category labels and classification of the studies in these categories were made on the basis of the software engineering activity that the literature studies have focused on.…”
Section: Software Development Area Research Studymentioning
confidence: 99%